2009
DOI: 10.1364/oe.17.000860
|View full text |Cite
|
Sign up to set email alerts
|

Empirical model of the photon path length for a single fiber reflectance spectroscopy device

Abstract: A reflectance spectroscopic device that utilizes a single fiber for both light delivery and collection has advantages over classical multi-fiber probes. This study presents a novel empirical relationship between the single fiber path length and the combined effect of both the absorption coefficient, mua (range: 0.1-6 mm-1), and the reduced scattering coefficient, micro's (range: 0.3 - 10 mm-1), for different anisotropy values (0.75 and 0.92), and is applicable to probes containing a wide range of fiber diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 21 publications
0
82
0
Order By: Relevance
“…Such approaches can be categorized into several different data types, as outlined in table 1. These [7][8][9] spectral derivative data multiple analyte analysis [10][11][12] fluorescence/excitation ratio fluorescence imaging [13][14][15] multi-distance data estimation of slopes with linear approximations robust tissue spectroscopy systems insensitive to slight shape changes [16][17][18] small-volume sampling scatter spectroscopy fibre probes with size less than effective scatter distance [19][20][21][22] absorption spectroscopy fibre probes sensitive to absorption only [23,24] fluorescence spectroscopy fibre probes sensitive to fluorescence and not tissue [25,26] temporal signals millisecond variations in tissue oxygen saturation and haemodynamic sampling [8,27,28] microsecond sampling flash photolysis analysis of biochemical changes in vivo [29,30] picosecond sampling ultrafast signals to reduce model dependence [31][32][33][34][35] high-frequency phase shift derivative with distance frequency-domain spectroscopy of tissue [36,37] lifetime-based signals fluorophore identification or microenvironment analysis [38] include: (i) ratiometric or derivative data at two or more different wavelengths, (ii) multiple-distance ratio or derivative data, (iii) small spatial volumes that either limit the effect of physical boundaries through scatter and/or absorption, or allow simpler empirical modelling, and (iv) temporal signals that are less sensitive to boundaries and/or more robustly insensitive to shape changes. The use of prior information about the tissue to be sampled is still essential in the design process with these systems, but can be implemented in the very first step o...…”
Section: Prior Information: Structure (A) External Shape and Internalmentioning
confidence: 99%
“…Such approaches can be categorized into several different data types, as outlined in table 1. These [7][8][9] spectral derivative data multiple analyte analysis [10][11][12] fluorescence/excitation ratio fluorescence imaging [13][14][15] multi-distance data estimation of slopes with linear approximations robust tissue spectroscopy systems insensitive to slight shape changes [16][17][18] small-volume sampling scatter spectroscopy fibre probes with size less than effective scatter distance [19][20][21][22] absorption spectroscopy fibre probes sensitive to absorption only [23,24] fluorescence spectroscopy fibre probes sensitive to fluorescence and not tissue [25,26] temporal signals millisecond variations in tissue oxygen saturation and haemodynamic sampling [8,27,28] microsecond sampling flash photolysis analysis of biochemical changes in vivo [29,30] picosecond sampling ultrafast signals to reduce model dependence [31][32][33][34][35] high-frequency phase shift derivative with distance frequency-domain spectroscopy of tissue [36,37] lifetime-based signals fluorophore identification or microenvironment analysis [38] include: (i) ratiometric or derivative data at two or more different wavelengths, (ii) multiple-distance ratio or derivative data, (iii) small spatial volumes that either limit the effect of physical boundaries through scatter and/or absorption, or allow simpler empirical modelling, and (iv) temporal signals that are less sensitive to boundaries and/or more robustly insensitive to shape changes. The use of prior information about the tissue to be sampled is still essential in the design process with these systems, but can be implemented in the very first step o...…”
Section: Prior Information: Structure (A) External Shape and Internalmentioning
confidence: 99%
“…Path length equivalence was verified by measuring <L SFR > using Eq. 1 as in previous studies (5,19), where…”
Section: System Validationmentioning
confidence: 74%
“…In this geometry, the measurement volume is confined to shallow depths on the order of the fiber diameter, dependent on the optical properties (4,5), and the measurement is sensitive to the scattering phase function (6). As such, SFR spectroscopy may be well suited for detection of localized changes to tissue microstructure that are expected to accompany early onset of disease.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] However, recent work showed that a range of γ values (for the same μ 0 s , μ a , and d det ) can result in the same reflectance.…”
Section: Introductionmentioning
confidence: 99%